(untitled) (Journal of the Bangladesh Agricultural University, 2011)
The anti fungal effects of some plants extracts namely tobacco leaf, keora seed, keora, mahogoni, gaint indian milky weed, garlic and ginger at different concentrations (30%, 40%, 50%, 60% and 70%) on the growth and development of C. gloeosporioides, causal agent of anthracnose of mango were evaluated. Radial growth of C. gloeosporioides was recorded. The growth inhibition increase with the increase of concentration of all the plant extracts. Highest mycelial growth inhibition (74.35%) was observed in case of garlic extracts at 70% concentration. Garlic extract at 50% and 60% concentration were also effective than other treatments. Keywords: C. Gloeosporiodes; Plant extracts; Inhibition DOI: http://dx.doi.org/10.3329/jbau.v9i1.8742 JBAU 2011; 9(1): 43-47